Global prevalence of burnout symptoms among nurses: A systematic review and meta-analysis. (April 2020) - Woo, Tiffany; Ho, Roger; Tang, Arthur; Tam, Wilson
Abstract: WHO recently declared burnout as a "occupational phenomenon" in the International Classification of Diseases 11th revision (ICD-11), recognizing burnout as a serious health issue. Amongst healthcare workers, nurses are known to struggle with burnout symptoms the most, carrying serious consequences for patients, other healthcare professionals and healthcare organisations. Evidence has suggested that burnout symptoms in nurses is high across specialties and countries, but no meta-analysis have been performed to investigate burnout symptoms prevalence in nurses globally. We conducted a systematic review and meta-analysis to examine burnout symptoms prevalence in nurses worldwide using 8 academic research databases. Risk of bias, heterogeneity and subgroup analyses were further conducted in the meta-analysis. 113 studies were included for systematic review and 61 studies for the meta-analysis, consisting 45, 539 nurses worldwide in 49 countries across multiple specialties. An overall pooled-prevalence of burnout symptoms among global nurses was 11.23%. Significant differences were noted between geographical regions, specialties and type of burnout measurement used. Sub-Saharan African region had the highest burnout symptoms prevalence rate while Europe and Central Asia region had the lowest. Paediatric nurses had the highest burnout symptoms prevalence rates among all specialties while Geriatric care nurses had the lowest. This study is the first study to synthesize published studies and to estimate pooled-prevalence of burnout symptoms among nurses globally. The findings suggest that nurses have high burnout symptoms prevalence warranting attention and implementation. This study serves as an impetus for intervention studies and policy change to improve nurses' work conditions and overall healthcare quality. Graphical abstract: Image 1